Examination of surgical and conservative treatment effects on depression of patients with moderate carpal tunnel syndrome - Güvenç, Kenan; Ilik, Kemal; Ilik, Faik; Gönen, Murat; Kayhan, Fatih (My University, 2019)
Objective: The aim of this study is to examine the outcomes of conservative and surgical treatments of patientswith carpal tunnel syndrome as well as the effects of these two treatment options on depressive symptoms ofthese patients.Methods: A case-control study carried out from June 2015 to Fabruary 2016 and 111 moderate moderate carpaltunnel syndrome patients were included in the study whose diagnosis was confirmed by electroneuromyography(ENMG). The 78 of the patients had surgical treatment and 33 of them, who did not accept the surgery, receivedsteroids via injection and splinting technique was performed for 8 weeks. Boston Carpal Tunnel Questionnaire,quick disabilities of the arm, shoulder and hand score and Beck Depression Invertory scales were applied sixmonths before and after treatments.Results: It was detected that pain functional assessment scores and Beck depression scores significantlyrecovered the disease in patients who had surgical treatment compared to ones who had the conservativetreatment.Conclusions: It can be concluded that surgical treatment plays a more active role in the recovery of depressivesymptoms in patients with moderate carpal tunnel syndrome.
Keywords: Psikoloji; Cerrahi